(untitled) (Nigerian Journal of Technology, 2019)
The study investigates the effects of building collapse risks on the stakeholders in the Nigerian built environment. Survey research design was adopted in carrying out the research and five cities in Nigeria were selected (Abuja, Ibadan, Port Harcourt, Owerri and Lagos). The target population for the study is the stakeholders in the Nigerian built environment: key professionals in the construction industry, clients/developers and users of the finished product. A sample size of 1999 was chosen using Taro Yamane method. The data generated from 1860 respondents representing 93 % of the distributed questionnaires were presented using frequency tables, pie –charts and bar charts, while analysis was done using percentages and weighted mean. The findings of the study show that building collapse risks have multifarious factors which were categorized as Economic/Financial risks, Socio-political risks, Human related risks, Physical risks, Environmental risks and Law/legal risks. The negative effects of these risks are: loss of property, loss of reputation and integrity of the contractors, loss of lives, legal tussle among the stakeholders, etc.. It was also found out that economic/financial risks have the predominant effect on the stakeholders, followed by Human related risks, Socio-Political risks, Physical risks, Environmental risks and lastly Law/Legal risks. It was recommended that all hands should be on deck to curb the havoc caused by building collapse as the effect is usually felt by all and sundry. There should be adequate funding and monitoring of the activities of all Emergency Management Agencies. http://dx.doi.org/10.4314/njt.v38i4.2